Bacillus subtilis RecO and SsbA are crucial for RecA-mediated recombinational DNA repair. Issue 12 (22nd May 2015) - Carrasco, Begoña; Yadav, Tribhuwan; Serrano, Ester; Alonso, Juan C.
Abstract: Genetic data have revealed that the absence of Bacillus subtilis RecO and one of the end-processing avenues (AddAB or RecJ) renders cells as sensitive to DNA damaging agents as the null recA, suggesting that both end-resection pathways require RecO for recombination. RecA, in the rATP·Mg 2+ bound form (RecA·ATP), is inactive to catalyze DNA recombination between linear double-stranded (ds) DNA and naked complementary circular single-stranded (ss) DNA. We showed that RecA·ATP could not nucleate and/or polymerize on SsbA·ssDNA or SsbB·ssDNA complexes. RecA·ATP nucleates and polymerizes on RecO·ssDNA·SsbA complexes more efficiently than on RecO·ssDNA·SsbB complexes. Limiting SsbA concentrations were sufficient to stimulate RecA·ATP assembly on the RecO·ssDNA·SsbB complexes. RecO and SsbA are necessary and sufficient to 'activate' RecA·ATP to catalyze DNA strand exchange, whereas the AddAB complex, RecO alone or in concert with SsbB was not sufficient. In presence of AddAB, RecO and SsbA are still necessary for efficient RecA·ATP-mediated three-strand exchange recombination. Based on genetic and biochemical data, we proposed that SsbA and RecO (or SsbA, RecO and RecR in vivo ) are crucial for RecA activation for both, AddAB and RecJ–RecQ (RecS) recombinational repair pathways.